Designing model of the music art training for teacher of art and culture based on active learning - Iswandi Iswandi; Yasri Yasri; Nurhizrah Gistituati; Ardipal Ardipal (Fakultas Ilmu Pendidikan UNP)
This research motivated by the problems faced by teachers of art and culture subjects of Senior High School in the Province of West Sumatra namely the low results of Teacher Competency Test with an average score of 60 in particular the field art of music. The purpose of this model design is to develop a model of music art training that is valid, practical, and effective. Research method used is Research and Development with ADDIE procedures. The sample is determined by area probability sampling technique with the number of respondents 34 teachers of arts and culture subjects. The results concluded that the average of the ability of teachers 58.75. The developed model design consists of: (1) preparation stage (training contract, ability analysis, and group division); (2) learning stages (finding concepts/theories, discussions, group demonstrations, peer feedback, training with instructor's guidance, joint demonstrations); (3) evaluation stage through observation test.